Ulcer of Marjolin. Case report - Ninecta Pérez Breña; Maileidys Aguila López; Naivy Sanchez Vera (Acta Médica del Centro)
Introduction: Marjolin's ulcer is the result of malignant degeneration of post-burn scars. Its evolution is fatal if the diagnosis is late. Case Report: An 84-year-old patient was presented with a history of suffering from accidental burn injuries on 34% of her body from direct fire since she was 13 years old.  Recently she went to consultation for presenting a tumor on her face and her left shoulder on the old burned scar. An excisional biopsy was performed, with histopathological result of ulcerated squamous cell carcinoma, It was decided to performed exceresis of them. Her evolution was favorable without complications. Conclusions: A patient with a diagnosis of a Marjolin’s ulcer with a favorable evolution after removal was presented, which is considered of interest to medicine due to the novelty of the case and with the objetive of contributing to the timely diagnosis of this sickness.